SISTEM INFORMASI GEOGRAFIS PENYEBARAN PENDUDUK DI KECAMATAN RAMBUTAN UNTUK ANALISA DI BIDANG KEPENDUDUKAN - Ariandi, Muhammad ; Agustini, Eka Puji (JURNAL ILMIAH MATRIK, 2018)
Geographic Information System (GIS) is an information technology developed to know a location based on geographical location. One of them is Rambutan District whose population data has not been shown in the form of geographic information system, so that the decision maker is difficult to know the spreading of population in that sub-district. In this research will be made Geographic Information System Population Dissemination which will show the data of the number of male population and the number of female population, the number of population of children at school age, and the number of population per village in Rambutan District. This research uses action research method with five stages that will be done. Keywords: GIS, Population, Data Dissemination, Action Research